Pengaruh Perubahan Penggunaan Lahan Sub DAS Rawapening terhadap Erosi dan Sedimentasi Danau Rawapening - Aprilliyana, Dian (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
Indonesian Lake National Conference or â€œKNDIâ€ in Bali on 2009 decided to put Rawapening Lake as one of 15 (fifteen) lakes/dams that need to be prioritize in Indonesian lake revitalisation. Land use change issues in Rawapening Sub-watershed area has been emerging as the main issues behind land degradation that created erosion. Erosion in the end affected the level of Rawapening lake sedimentation. This research use quantitative positivistic approach with descriptive method as the analytical methodology. The method will be use to desribe the existing variables and phenomenons. The erosion and sedimentation calculation result showing if the erosion and sedimentation in Rawapening Lake are decrease. It caused by several dynamic factors within analysis process. In order to identify the influence of land use change toward erotion and sedimentation, it used erosivity average value for about 2.523,9. The analysis result showing that falling number of non-built-up area or â€œtegakanâ€ vice versa with the erosion rate, total number of erosion, and sedimentation. In the other hand, the number of built-up area in line with the erosion rate, total number of erosion, and sedimentation. Land use change that created the biggest erosion rate enhancement is land use change from â€œtegakanâ€ to built-up area and land use change from farmland to built-up area.